Effects of roasting temperature and time on aldehyde formation derived from lipid oxidation in scallop (Patinopecten yessoensis) and the deterrent effect by antioxidants of bamboo leaves. (1st February 2022) - Hu, Yuanyuan; Zhao, Guanhua; Yin, Fawen; Liu, Zhongyuan; Wang, Jialiang; Qin, Lei; Zhou, Dayong; Shahidi, Fereidoon; Zhu, Beiwei
Highlights: Roasting process increased lipid oxidation and aldehyde generation in scallops. Most aldehydes increased in a time- and temperature-dependent manner. Antioxidants of bamboo leaves reduced aldehyde formation during roasting process. Antioxidants of bamboo leaves retarded the oxidation of polyunsaturated fatty acids. Antioxidants of bamboo leaves inhibited the formation of free radicals. Abstract: This study aimed to investigate the effects of roasting temperature and time on aldehyde formation derived from lipid oxidation in scallop, and the deterrent effect of natural antioxidants extracted from bamboo leaves (AOB). Results showed that roasting process significantly increased the peroxide value (PV), thiobarbituric acid-reactive substances (TBARS), p- Anisidine value ( p- AV), and total oxidation (TOTOX) in scallop lipids. Besides, 16 different aldehydes in scallop lipids were detected using an HPLC-ESI-MS/MS method. Among them, the content of hexanal, pentanal, nonanal, trans, trans -2, 4-octadienal, and 4-hydroxy-2-hexenal increased in a time- and temperature-dependent manner during the roasting process. After roasting at 210 °C for 40 min, their content increased by 1.23, 0.81, 1.44, 0.59, and 2.12 folds compared with the unroasted group, respectively. However, pretreatment with AOB effectively prevented aldehyde formation in roasted scallops by reducing the oxidation of polyunsaturated fatty acids and scavenging free radicals.